The Fosen Case and the Protection of Sámi Culture in Norway Pursuant to Article 27 ICCPR - Ravna, Øyvind (International Journal on Minority and Group Rights, 2022)
The International Covenant on Civil and Political Rights has been a part of Norwegian law since 1999. It has, however, been of greater importance in the political sphere than in the courts. In the fall of 2021, the Supreme Court of ruled that the construction of two wind power plants were violating the rights of Indigenous Sámi reindeer herders pursuant to the Article 27 ICCPR. In the presentation, the Supreme Court’s use of Article 27 is analysed in order to determine its impact on protecting Indigenous rights in Norway, including where the threshold for violation lays when interference in Sámi reindeer husbandry areas take place.